Comparison of in vitro erosion protocols in bovine teeth to simulate natural erosion lesion: analysis of mechanical properties and surface gloss - Mariana Dias Moda; Ticiane Cestari Fagundes; Eduardo Bresciani; André Luiz Fraga Briso; Paulo Henrique Dos Santos (University of São Paulo, 2019)
Abstract Objective The aim of this study was to compare two in vitro erosion protocols, in which one simulates in vivo conditions experienced by patients with gastroesophageal disorders or bulimia (HCl-pepsin protocol), and the other simulates the diet of an individual who consumes a high volume of erosive beverages (citric acid protocol). In addition, the mechanical properties and surface gloss of eroded human dentin were compared with those of sound human dentin. Materials and Methods Blocks of cervical dentin were used: sound human dentin (n=10), human dentin with erosive lesions (n=10), and bovine dentin (n=30). Twenty bovine blocks were subjected to either of two erosion protocols (n=10/protocol). In the first protocol, samples were demineralized using HCl-pepsin solution, then treated with trypsin solution. In the second protocol, samples were demineralized with 2% citric acid. Toothbrushing was performed in both protocols using a toothbrushing machine (15 s with a 150 g load). Ten bovine dentin blocks were not subjected to any erosive treatment. All samples of bovine and human dentin were analyzed to obtain Martens hardness values (MH), elastic modulus (Eit*) and surface gloss. One-way ANOVA and Tukey's test were performed to analyze the data (α=0.05). Results Sound human and eroded human dentin groups showed similar MH and Eit* values (p>0.05); however, sound human dentin showed a higher surface gloss value when compared to eroded human dentin (p<0.05). Sound bovine dentin and HCl-pepsin-treated bovine dentin treatments resulted in similar values for both MH and Eit* (p>0.05), but HCl-pepsin-treated bovine dentin and citric acid-treated bovine dentin resulted in lower surface gloss than sound bovine dentin (p<0.05). Conclusions The HCl-pepsin protocol modified bovine dentin properties that could be similar to those that occur on human dentin surfaces with erosive lesions.